SOME INDICATORS OF DENTAL CARE IN PRIVATE INSTITUTIONS OF THE KIROVOHRAD REGION - S.I. Dramaretska; V.V. Yevchyk (Український стоматологічний альманах)
Relevance. Global upheavals in the country affected the activities of dental institutions, including private ones.